Revolusi Digital UMKM : Membuka Peluang Pasar Lebih Luas Melalui Media Sosial dan E-commerce di Desa Kedungjambe - Novita Sari Makigawe; Maharani Ikaningtyas (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the impact of digital marketing training focused on the utilization of WhatsApp Business and Shopee in driving the digital transformation of Micro, Small, and Medium Enterprises (MSMEs) in the food sector in Kedungjambe Village. Using both quantitative and qualitative approaches, the research evaluates the effectiveness of training on creating engaging promotional content on WhatsApp Business and managing online stores on Shopee to enhance product visibility, expand market reach, and improve MSME sales performance. The findings reveal that equipping MSMEs with skills to optimize features on these platforms, such as creating appealing product catalogs, utilizing broadcast features, and managing online stores effectively on Shopee, significantly enhances customer interaction and the competitiveness of MSMEs in the digital era. In addition to positively impacting sales growth, the training also accelerates digital technology adoption among MSMEs, enabling them to compete more effectively in an increasingly competitive market. These findings highlight the importance of targeted and sustainable training programs in supporting the growth of MSMEs in the digital age.